Geofísica aplicada na avaliação de recursos hídricos subterrâneos e meio ambiente da zona costeira do campo petrolífero de fazenda Alegre, norte Capixaba Espírito Santo - Leal, Claudio Antonio (2007)
The overall objective of the research was the evaluation of Fazenda Alegre oil and gas production field area groundwater resources, on the north of the Espírito Santo State coastal area. Geophysical techniques, integrated with hydro-geological analysis, were applied in order to find reliable sources of water for utilization during secondary recovery of petroleum (steam injection) processes. Field production without stream injection is difficult because of the high oil viscosity. Application of geophysical techniques investigation integrated with lithological analysis and pumping tests of deep water wells identified six geoelectric layers, being the 3rd and the 5th the most promising, regarding to the potential for groundwater production. From the results of geophysical analysis and data integration some deep water well sites were proposed. Two wells, denominated FAL-40 and FAL-42, were drilled down to 180 meters levels in order to verify the validation of the results of the proposed model for optimization of groundwater production with the least number of wells pumped. Pumping tests of these two wells presented excellent results being verified that it can be maintained a production of 110 m3/h during daily 20 hours continuous pumping periods, hence verifying the expected good groundwater aquifer system available. It was concluded that the application of the results of the hydrogeological study developed during the research can contribute to the rational exploration of the aquifer system and to the sustainable development of the region.